2022
DOI: 10.3390/plants11121606
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of Silicon Supply on Root Sulfur Uptake in S-Fed and S-Deprived Brassica napus L.

Abstract: Silicon (Si) is known to alleviate many nutritional stresses. However, in Brassica napus, which is a highly S-demanding species, the Si effect on S deficiency remains undocumented. The aim of this study was to assess whether Si alleviates the negative effects of S deficiency on Brassica napus and modulates root sulfate uptake capacity and S accumulation. For this, Brassica napus plants were cultivated with or without S and supplied or not supplied with Si. The effects of Si on S content, growth, expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…This study demonstrated that the growth of Trifolium incarnatum was not affected by S deficiency during the 21 first days of treatment ( Figure 1 ). This result agrees with previous work performed in Brassica napus cultivated in hydroponic conditions and subjected to the same duration of S-deprivation [ 28 ]. In contrast, when the S-deprivation was prolonged (D63), this study showed that a strong decrease in both shoot and total biomasses occurred in -S-Si plants compared to +S-Si plants ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study demonstrated that the growth of Trifolium incarnatum was not affected by S deficiency during the 21 first days of treatment ( Figure 1 ). This result agrees with previous work performed in Brassica napus cultivated in hydroponic conditions and subjected to the same duration of S-deprivation [ 28 ]. In contrast, when the S-deprivation was prolonged (D63), this study showed that a strong decrease in both shoot and total biomasses occurred in -S-Si plants compared to +S-Si plants ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…Silicon is largely known to alleviate negative effects of abiotic stress in plants [ 26 , 28 , 35 , 36 ] and to improve plant health [ 30 ]. However, the effect of Si supply on S-deprived plants is currently poorly documented, as reported by [ 27 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in rapeseed, Si has been shown to alleviate the effect of nitrogen deficiency by delaying leaf senescence and promoting the expression of N transporters [38]. Nevertheless, in a recent study, no clear positive influence of Si could be observed in rapeseed plants under S deficiency: Si supply did not increase the biomass or S content in these conditions [39]. Regarding B and Si interaction, most of the work has been focused on the effect of Si in alleviating B toxicity [40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 92%